Impact of COVID-19 on Ophthalmologists - Wajeeha Rasool , Kanwal Zareen Abbasi , Maria Zubair ,Misbah Munshi ,Rehmah Sarfraz , Fuad A K Niazi (Journal of Rawalpindi Medical College, 2021)
Objectives: To determine the effects of COVID 19 pandemic on the professional lives of ophthalmologists Methods: This cross sectional survey was conducted for 6 months in late 2020 and used google forms for data collection. Results: Total 68 respondents gave their likert response for each of the 20 statements. No. %, median, mode and interquartile range, of all respondents likert sentiment for each statement, were calculated. Survey results showed general, ‘consent and consensus’. Conclusion: Covid-19 has influenced professional lives of ophthalmologists.